Characterization of Blends of Petrol and Bioethanol Synthesized from Nigerian Palm Bunch. - Igbokwe, J. O.; Onuoha, L. N.; Nwafor, M. O. I.; Aviara, N. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study investigated fuel properties of pure petrol blended with bioethanol produced from Nigerian waste palm bunch. The produced bioethanol was blended with pure petrol at volume percentage ratio of 0:100, 10:90, 20:80, 30:70, 40:60, 50:50, 60:40 and 100:0 to obtain E0, E10, E20, E30, E40, E50, E60 and E100 blend respectively. These were then characterized for fuel properties base on ASTM standard. The result confirmed that fuel properties of bioethanol produced from Nigerian waste palm bunch met the International Standard as established by ASTM for use in SI engine. The blends improved the fuel properties of pure petrol. Density of the blends increased as the percentage of bioethanol increases in the blends. Octane number of pure petrol increased with increase in bioethanol in the blends. Flash point of all the blends was below 15 oC making them susceptible to ignition and having the chance of flammability hazard. 10 % bioethanol increased the blend’s vapor pressure to a peak value of 53 kPa which declined with further increase of bioethanol percentage. The bioethanol increased viscosity of pure petrol. Calorific value of pure petrol was decreased with increase in the bioethanol content.